Influence of Bi₂O₃ content on thermal, structural and optical properties of bismuth tellurite glass-ceramics by controlled heat treatment for optical applications - Fong, Wai Leng (2021)
This dissertation has summarized the findings of the thermal, structural, and optical properties in xBi2O3-5Na2O-5TiO2-10ZnO-(80-x)TeO2 based glass, where x= 5, 8, 10, 12, and 15mol% by using the melt quenching method. Multiples techniques have been carried on to characterize the influence of the Bi2O3 content on the thermal, structural, and optical properties of the bismuth tellurite based glass. The thermal properties have been analyzed by differential scanning calorimetry to identify the glass transition temperature, Tg, onset crystallization temperature, Tx, and crystallization temperature, Tc. The increasing Bi2O3 content causes the Tg to decrease due to the decomposition of strong TeO4 units into TeO3+1 polyhedra and TeO3 units and the replacement of strong Te-O-Te bonds by the formation of weaker Te-O-Bi bonds and Bi-O-Bi bonds. The formation of BiO3 and BiO6 can be observed when reaching an optimum percentage of Bi2O3. The Bi-rich phase will enhance the rate of nucleation and crystals growth rate which improve the crystallization tendency of the glass samples. Thus, a greater tendency for the glass ceramics transformation. The high content of Bi2O3 has caused the glass ceramics to lose transparency due to the oversize crystalline growth. On the other hand, the structural changes based on the variation of composition also investigated by X-Ray diffraction (XRD), Raman spectroscopy, and Fourier transform infrared (FTIR). The results from the structural analysis have proven the formation of BiO3 and BiO6 units. The formation of BiO3 and BiO6 units with more open structure has increased with the increasing percentage of Bi2O3. The more open structures have further improved the rate of nucleation and crystal growth within the glass matrix. Thus, the higher content of Bi2O3 has favoured the glass ceramics transformation. As a result of the heat treated sample glasses, the Bi2O3 content was strongly affecting the transparency of the resultant glass-ceramics due to the crystallization behaviour of the Bi2O3. The types of crystal formed within the glass matrix after controlled heat treatment were identified through X-ray diffraction (XRD). The Bi2O3.96 crystal started to form within the glass matrix with a lower Bi2O3 content and the transparency of the glass-ceramics was retained in these samples. Sample glass-ceramics were started to turn opaque on the samples with high Bi2O3 content with the formation of β-Bi2O3 crystals. Besides that, the vibration modes of the structural units and the functional group of the elements before and after the controlled heat treatment were identified by Raman and FTIR. In addition, the optical properties including the direct and indirect energy bandgap, Eg which induced optically by the incident photons of the amorphous nature before controlled heat treatment, and the crystalline structure after the heat treatment were investigated through the UV-Visible absorption spectrophotometer. The energy bandgap, Eg has decreased due to the high concentration of NBO within the glass network which increases the excitation tendency of the electrons to the conduction band as the content of Bi2O3 increased. The sharp absorption edge can be observed in the heat treated glass and the sample glass ceramics with 12mol% and 15mol% Bi2O3 content have the most significant absorption edge as compared with the lower Bi2O3 content. The wavelength transmission in visible wavelength were extremely low in sample glass ceramics with 12mol% and 15 mol% of Bi2O3 content. Thus, the transparency of these sample glass ceramics were extremely low. The optical bandgap also reduced more in sample glass ceramics with greater Bi2O3 content as compared with the sample glasses. Most importantly, the transparency of the bismuth tellurite glass-ceramics has to be maintained above 50% for optical applications. The transparency of the samples started to decreased and turned opaque by the increasing Bi2O3 content and longer heat treatment period. The crystal growth of the tellurite glass-ceramics also has been investigated by using the Field Emission Scanning Electron Microscope. In conclusion, the optimum Bi2O3 content was 10mol% which has a significant crystallization tendency that showing 2 significant crystallization peaks. The 10 mol% glass ceramics having optimized glass ceramics properties with an excellent transparency at the same time. However, the heat treatment period has to be monitored to prevent the overgrowth of crystal which directly affecting the transparency of glass ceramics.